Alternative Dietary Fiber Sources from Kenaf (Hibiscus cannabinus L.) Seeds and Their by-Products - Nevara, Gita Addelia; Sharifah Kharidah Syed Muhammad; Norhasnida Zawawi; Nor Afizah Mustapha; Roselina Karim (Jurnal Gizi dan Pangan, 2022)
This study evaluates the macronutrients and Dietary Fiber (DF) of kenaf seeds and their secondary by-products to promote food sustainability and support the zero-waste concept. The first part concentrates on macronutrients and potential DF sources of kenaf seeds and their by-products, i.e., kenaf seed meals and dregs. Following this, the DF from the most probable source was fractionated to quantify its composition. The results showed that the macronutrients of kenaf seeds are comparable to other commercial oilseeds such as soybean, almond, and hemp seeds. Additionally, the secondary by-products could be reused as DF sources. It was found that the kenaf seed by-products had 20.63–35.08% DF contents which were comparable to soybean by-products. Moreover, the fractionation of DF from kenaf seed dregs showed that the DF comprised 1.86%, 1.01%, 6.33%, and 66.33% (dry basis) of acid-soluble pectin, calcium-bound pectin, alkali-soluble hemicellulose, and cellulose, respectively. The soluble (pectins and hemicelluloses) and insoluble (cellulose) fractions are related to the modulation of gut microbiota which have similar potential to conventional prebiotics and an excellent role in bodyweight management, respectively. These findings provide useful information for researchers and industries to venture into alternative DF sources from kenaf seeds as a value-add ingredient for functional food applications.